Effect of Gestational Age and Nutrition on Transplacental Transfer of Measles Antibody - Kamar, S; Chowdhury, POA; Murshed, M; Hassan, R (Medicine Today, 2012)
Medicine Today 2009 Volume 21 Number 02 Page 77-81 DOI: http://dx.doi.org/10.3329/medtoday.v21i2.12553